Orthopedic Injuries Associated with Hoverboard Use in Children: A Multi-center Analysis. Issue 2 (December 2020) - Goldhaber, Nicole H.; Goldin, Amanda N.; Pennock, Andrew T.; Livingston, Kristin; Bae, Donald S.; Yen, Yi Meng; Shore, Benjamin J.; Kramer, Dennis E.; Jagodzinski, Jason E.; Heyworth, Benton E.
Background: Since its release in 2015, the hoverboard has been associated with injuries in children and adolescents. However, its public health implications have yet to be explored in the orthopedic literature across multiple centers. Purpose/Questions: We sought to assess the nature of orthopedic injuries and the use of clinical resources related to the hoverboard at four high-volume, regional pediatric hospitals. Methods: Departmental databases of emergency department (ED) consultations and urgent orthopedic clinic (UC) visits were queried for hoverboard injuries. A retrospective medical record review was performed for patients presenting over a 3-month period at four institutions. Data on demographics, injuries, clinical course, and resource use were analyzed. The frequency of hoverboard-related consultations was compared to those for monkey bar–related injuries at the primary study institution. Results: Eighty-nine patients with orthopedic hoverboard injuries presented to the ED and/or UC in the study period. Hoverboard injuries represented 2.2% of orthopedic ED consultations at the primary institution, compared to 1.5% for monkey bar injuries. Sixty-nine out of 89 (77.5%) total injuries involved the upper extremity, including 47 (52.8%) distal radius fractures, the most common hoverboard–related diagnosis. All but one injury (97.8%) underwent radiography, and eight (9%) required surgery. No patients reported wearing protective gear at the time of their injury. Conclusions: Hoverboards were associated with a variety of pediatric orthopedic injuries and required the use of significant resources in the ED, UC, and operating room. These data may represent a starting point for further prospective multi-center studies and public health efforts toward prevention of hoverboard injuries.